PENGENALAN DASAR MISCROSOFT WORD PADA SISWA SISWI SMP MA’ARIF NU 1 PUURWOKERTO - Elza Nabila Zain; Sah Aldiana; Fatihatu Ufriza; Ririn Marwaningsih; Ito Setiawan (JOURNAL SAINS STUDENT RESEARCH, 2026)
Digital literacy is a fundamental competence that must be mastered from an early age, especially in technology-based learning contexts. This study examines the effectiveness of a Microsoft Word basic introduction socialization program on improving the understanding and skills of students at SMP Ma'arif NU 1 Purwokerto. Using a qualitative descriptive approach with a quasi-experimental design (pretest-posttest one group design), data were collected through written tests, participatory observation, and in-depth interviews with 32 seventh-grade students. The results showed an average improvement in comprehension scores of 41.2% (from 54.3 to 76.7), with 78.1% of students achieving the minimum competency criteria. The direct demonstration method combined with guided independent practice proved most effective in improving students' operational competencies. These findings affirm the urgency of integrating digital literacy training in the secondary school curriculum, while recommending a practice-based learning model as a measurable and sustainable intervention strategy.